Growth dynamics and body size evolution of South American long-necked chelid turtles: a bone histology approach - Pereyra, Maria Eugenia (2020)
Among turtles, cases of ?gigantism? occur mostly in pleurodiran Pelomedusoides and cryptodirans, but are infrequentamong pleurodiran chelids, which are mostly small-medium sized turtles. Yaminuechelys spp. are extinct South Americanlong-necked chelids (from the Late Cretaceous?early Paleocene of Patagonia, Argentina) with caparaces almost threetimes larger than their extant sister taxon, Hydromedusa tectifera. Since evolutionary changes in size can be analyzedbased on growth dynamics, we studied growth strategies from an osteohistological point of view. We sampled bothextinct (Yaminuechelys maior) and extant (H. tectifera) species, in order to test hypotheses related to the mechanismsinvolved in the macroevolution of size within this clade. For this purpose, thin sections of long bone (humerus andfemur) shafts of specimens of different ontogenetic stages for these species were prepared. The osteohistological studyreveals a similar growth dynamic in both taxa, with a poorly vascularized cortex dominated by parallel- fibered boneand interrupted by lines of arrested growth (LAGs). The huge body size of Y. maior appears to be a consequence of theprolongation of the growth phase, suggesting that it had a longer lifespan than H. tectifera, allowing to reach greatersizes. In this way, and assuming that there is no displacement at the beginning of development (e.g., a delay in the earlieststages of growth) in H. tectifera, the acquisition of a large size in Yaminuechelys would be explained by hypomorphosisof the former or hypermorphosis of the latter, depending on the reconstruction of the ancestral condition of this clade.